Religiöse Vertreter - Friedensvermittler: zur Rolle religiöser Persönlichkeiten bei der Lösung bewaffneter Konflikte - Civico, Aldo (Zeitschrift für katholische Theologie, 2003)
During recent years representatives of religions have increasingly taken up a role in the mediation of conflicts. This fact is the occasion to highlight the conditions, procedures and possible outcomes of such mediations. Together with other recognized groups church representatives can achieve specific results because of the trust placed in them during this so called "second track diplomacy". However, this they have to experience and realize first in themselves.